Water for food systems and nutrition - Ringler, Claudia; Agbonlahor, Mure Uhunamure; Baye, Kaleab; Barron, Jennie; Hafeez, Mohsin; Lundqvist, Jan; Meenakshi, J.V.; Mehta, Lyla; Mekonnen, Dawit Kelemework; Rojas Ortuste, Franz; Tankibayeva, Aliya; Uhlenbrook, Stefan (Springer, 2023)
Access to sufficient and clean freshwater is essential for all life. Water is also essential for the functioning of food systems: as a key input into food production, but also in processing and preparation, and as a food itself. Water scarcity and pollution are growing, affecting poorer populations most, and particularly food producers. Malnutrition levels are also on the rise, and this is closely linked to water scarcity. The achievement of Sustainable Development Goals (SDG) 2 and 6 are co-dependent. Solutions for jointly improving food systems and water security outcomes include: (1) strengthening efforts to retain water-based ecosystems and their functions; (2) improving agricultural water management for better diets for all; (3) reducing water and food losses beyond the farmgate; (4) coordinating water with nutrition and health interventions; (5) increasing the environmental sustainability of food systems; (6) explicitly addressing social inequities in water-nutrition linkages; and (7) improving data quality and monitoring for water-food system linkages, drawing on innovations in information and communications technology (ICT). Climate change and other environmental and societal changes make the implementation and scaling of solutions more urgent than ever.